Postoperative Rehabilitation of Anterior Cruciate Ligament Reconstruction: A Systematic Review. Issue 2 (June 2021) - Nelson, Christopher; Rajan, Lavan; Day, Jonathan; Hinton, Richard; Bodendorfer, Blake M.
Abstract : Recent studies have investigated the various components of postoperative rehabilitation protocols following anterior cruciate ligament reconstruction (ACLR). The objective of this article was to access and summarize the latest evidence for postoperative rehabilitation protocols following ACLR to evaluate common timeframes, number of phases, exercises, as well as the length of rehabilitation protocol. Common interventions include vibration training, open-chain and closed-chain exercises, electrical stimulation, postoperative bracing, and aquatic therapy. The eligibility criteria included English-language articles published from 2000 to 2019 pertaining to rehabilitation following ACLR, excluding addresses, commentaries, and editorials. Two blinded reviewers screened, graded, and extracted data from articles. Recommendations on various aspects of rehabilitation were summarized. A total of 3651 articles were retrieved from the database search, and 62 level 1 to 2 studies were available for extraction. On the basis of the evidence, vibration training can be safely incorporated into the postoperative rehabilitation protocol following ACLR. Accelerated rehabilitation may give patients short-term functional benefits. Open kinetic chain exercises may have additional strength and endurance benefits. Postoperative bracing does not confer additional benefits. Long-term use of neuromuscular electrical stimulation seems to be more beneficial than short-term use. Aquatic rehabilitation may be beneficial in the early phases of anterior cruciate ligament rehabilitation. Abstract : Supplemental Digital Content is available in the text.